Fuel moisture content threshold leading to fire extinction under marginal conditions. (December 2020) - Awad, Carmen; Morvan, Dominique; Rossi, Jean-Louis; Marcelli, Thierry; Chatelon, François Joseph; Morandini, Fréderic; Balbi, Jacques-Henri
Abstract: This paper evaluates the fuel moisture content (FMC) threshold that leads to fire extinction for a few fuel types under marginal conditions. Influences of fuel load, fuel depth, Leaf Area Index (LAI) and packing ratio on this FMC threshold were also analyzed. This aim was reached by applying numerical simulations performed with three approaches: a simplified physical fire spread model, a detailed fire physical model and an empirical criterion. Experiments at laboratory scale were also performed. Moreover, some Results published in the literature over the last years were presented and compared with theoretical outputs.